Indonesian Translation and Validation of Co-Parenting Relationship Scale Brief Version (Brief-CRS) - Dewi Ilma Antawati; Bambang Raditya Purnomo (Qubahan Academic Journal)
The study aims to adapt the Brief-CRS scale and calculate the fit or not of the Brief-CRS measuring instrument for family respondents in Indonesia. The research applied quantitative approach through a cross-sectional research design. The samples of study were 179 fathers and mothers participating completed 14 items Brief Coparenting Relationship Scale (Brief-CRS).  The results indicated that 13-items measures reported in good reliability and strong stability. It shows that the psychometric properties and it’s positioned can promote further conceptual and methodological progress in the study of co-parenting in Indonesia.